The ELISA spectrometer at the JRC-Geel: development, achievements and future plans - Gkatis, Georgios; Pirovano, Elisa; Diakaki, Maria; Noguere, Gilles; Nyman, Markus; Oprea, Andreea; Paradela, Carlos; Plompen, Arjan (HNPS Advances in Nuclear Physics, 2024)
The ELISA (ELastic and Inelastic Scattering Array) setup, currently installed at the GELINA (Geel Electron Linear Accelerator) facility of the EC-JRC (European Commission – Joint Research Centre) in Geel (Belgium), is a unique instrument in Europe, used for the production of high-resolution neutron elastic and inelastic scattering cross-section data, relevant for nuclear physics applications. The setup features 32 liquid organic scintillators for the detection of the scattered neutrons coupled with a 235U ionization chamber for the measurement of the neutron flux. This paper outlines a brief history of the development of the setup, the measurements that have been performed so far, and the future experimental plans.